Efek Strategi Konflik Kognitif dalam Pembelajaran berbasis Model Inkuiri terhadap Kemampuan Berpikir Kritis Mahasiswa - Agus Muliadi; Saiful Prayogi; Baiq Mirawati; Irham Azmi; Ni Nyoman Sri Putu Verawati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2019)
The Effects of Conflict Cognitive Strategy in Inquiry-Based Learning Model on Students' Critical Thinking Ability. Critical thinking has become a very important part of learning at all levels of education, and learning based on inquiry activities is recommended as a teaching foundation for practicing critical thinking. Generating learners' prior knowledge in inquiry activities is needed with cognitive conflict strategies, and theoretical studies show that cognitive conflict strategies can improve learners to think critically. This study aims to determine the effect of cognitive conflict strategies in scientific inquiry learning on improving the critical thinking ability of physics prospective-teacher. This research is an experimental research (weak experimental research) with the design of "one group pretest-posttest design" with a sample of 21 physics prospective-teachers at IKIP Mataram. Critical thinking ability were measured using a critical thinking ability test instrument. Data on critical thinking ability were analyzed descriptively and statistically, where homogeneity, normality, and t-test were used. The results showed that the implementation of cognitive conflict strategies in inquiry learning models had an impact on critical thinking ability of physics prospective-teacher. Descriptions of the results of further research are described in this article.